The role of plant diversity and facilitation during tropical dry forest restoration - Fagundes, Marina V.; Mazzochini, Guilherme G.; Ganade, Gislene (The Journal of ecology, 2023)
Restoration programmes that promote the functioning of restored ecosystems are in urgent demand. Although several biodiversity and ecosystem functioning (BEF) experiments have demonstrated the importance of functional complementarity in enhancing plant community performance, no biodiversity experiment has yet manipulated facilitation to test its contribution to how the complementarity effect (CE) modulates community performance. We built a restoration experiment manipulating diversity and facilitation potential in a tropical semi‐arid forest. We planted 4704 seedlings of 16 native tree species to assemble 147 experimental communities with 45 different compositions comprising 1, 2, 4, 8 or 16 species. Facilitation potential was included in the experimental design by creating a gradient of communities from low to high facilitation potential (based on prior research). We measured functional dispersion and functional identity using species above‐ and below‐ground traits to investigate how they modulate the effects of species diversity and facilitation potential on leaf biomass production, using the additive partition biodiversity effects CE and selection effect (SE). The joint influence of diversity and facilitation potential was tested separately for leaf biomass production and net biodiversity effect using linear mixed models (LMMs). We subsequently ran LMMs including functional dispersion and functional identity. We hypothesised that facilitation potential would increase community productivity and functioning and that functional dispersion and functional identity related to above‐ and below‐ground traits would explain facilitation performance. Facilitation potential positively influenced leaf biomass production as predicted, but unexpectedly, neither of the functional traits were important for modulating the facilitation process. Positive values for CE showed that plants performed better in mixtures in comparison to monocultures. SE negative values, showed that species with below average performance in monocultures, performed better in mixtures. Unexpectedly, CE did not increase as species diversity or facilitation potential increased. The SE was influenced negatively by facilitation potential leading to a more equal distribution of biomass production between species in mixtures. Synthesis. Facilitation improves biomass production in restored communities and increases biomass equitability among plant species and thus ecosystem reliability. To improve restoration success, plant communities should be built using a combination of facilitative species. Resumo Os programas de restauração que promovem o funcionamento de ecossistemas restaurados são urgentes. Embora vários experimentos de biodiversidade e funcionamento de ecossistemas (BEF) tenham demonstrado a importância da complementaridade funcional em melhorar o desempenho da comunidade vegetal, nenhum estudo BEF manipulou ainda experimentalmente como o potencial de facilitação das espécies, modula o efeito de complementariedade e o desempenho das comunidades. Construímos um experimento de restauração manipulando a diversidade e o potencial de facilitação numa floresta semiárida tropical. Plantamos 4704 plântulas de 16 espécies de árvores nativas para montar 147 comunidades experimentais, com 45 composições diferentes compreendendo 1, 2, 4, 8 ou 16 espécies. O potencial de facilitação foi incluído no desenho experimental através da criação de um gradiente de comunidades de baixo a alto potencial de facilitação (com base em experimentos prévios). Medimos a dispersão funcional e a identidade funcional usando características de espécies acima e abaixo do solo para investigar como estas modulam os efeitos da diversidade de espécies e o potencial de facilitação na produção de biomassa foliar, usando os efeitos da partição aditiva da diversidade (CE) e o efeito de seleção (SE). A influência conjunta da diversidade e do potencial de facilitação foi testada separadamente para a produção de biomassa foliar e o efeito da biodiversidade líquida usando modelos mistos lineares (LMMs). Subsequentemente, foram realizados LMMs incluindo dispersão funcional e identidade funcional. Hipotetisamos que o potencial de facilitação aumentaria a produtividade e o funcionamento da comunidade e que a dispersão funcional e a identidade funcional relacionadas com as características funcionais acima e abaixo do solo explicariam o desempenho da facilitação. Os processos de facilitação influenciaram positivamente a produção de biomassa foliar como previsto, mas inesperadamente, nenhuma das características funcionais foi importante para modular o processo de facilitação. Os valores positivos para o efeito de complementaridade (CE) mostraram que as plantas tiveram um melhor desempenho em comunidades mistas em comparação com as monoculturas. Os valores negativos do efeito de seleção (SE), mostraram que as espécies com desempenho abaixo da média em monoculturas, tiveram um melhor desempenho em comunidades mistas. Inesperadamente, o CE não aumentou à medida que a diversidade ou facilitação de espécies aumentava. SE foi influenciado negativamente pelo potencial de facilitação, levando a uma distribuição mais igualitária da produção de biomassa entre espécies em misturas. Síntese. A facilitação melhora a produção de biomassa em comunidades restauradas e aumenta a equitabilidade da biomassa entre as espécies vegetais e, portanto, a confiabilidade do ecossistema. Para melhorar o sucesso da restauração, as comunidades vegetais devem ser construídas utilizando plantas facilitadoras. Facilitation improves biomass production in restored communities and increases biomass equitability among plant species and thus ecosystem reliability. To improve restoration success, plant communities should be built using a combination of facilitative plants.